PENGEMBANGAN LKPD BERBASIS PBL DENGAN LANGKAH POLYA UNTUK MEMBANTU SISWA MENYELESAIKAN MASALAH PROGRAM LINIER - Siti Farisma; Yudi Yunika Putra; Fitri Apriani (Jurnal Karya Pendidikan Matematika, 2023)
This paper focuses on the development of valid, practicable, and effectively developed LKPD based on the PBL learning model and Polya's problem-solving steps. This research is a 4D model of R&D with the implementation of definition, design, development, and dissemination stages. This research was implemented in a senior high school in Pemali Sub-district with the research subjects being six eleventh-grade students of the Social Studies-3 department for the small group trial and thirty-four eleventh-grade students of the Social Studies-4 department for the large group trial. The method of data gathering used was by conducting interviews, completing questionnaires, and taking written tests. The techniques of data analyzed were descriptively qualitative for the interviews and measurable quantitative for the questionnaires and written tests. The outcome of the data analysis revealed that the LKPD's average validity was 86.67 points with the most highly valid criteria, the practice of LKPD was 89.17 points with the most practical criteria, and the average normalized gain value (N-gain) of LKPD was 0.55 points with the interpretation of the medium effectiveness. In conclusion, PBL-based LKPD with the steps of Polya meets the criteria for developing teaching materials and can help students in solving Linear Program problems.